Knowledge and Attitude towards Prevention and Management of Hypertension in Jatinangor Sub-district - Malahayati, Kartika; Supriyadi, Rudi; Sastramihardja, Herri S. (Althea Medical Journal, 2016)
Background: There is an increase in prevalence of hypertension all over the world as well as Indonesia.Â Hypertension affects almost all body organs and systems. Hypertension prevention and management areÂ influenced by knowledge and attitude towards the disease. The aim of this study was to assess knowledgeÂ and attitude towards prevention and management of hypertension.Methods: This was a descriptive study with crossâsectional approach conducted in Jatinangor sub-district inÂ 2013. Sample sizes were determined based on proportion of the case in population and precision estimatesÂ (95% confidence intervals). One hundred twenty respondents aged 18â60 year-old were selected fromÂ population using stratified random sampling method. Hypertensions knowledge and attitude were assessedÂ using validated questioner as the scale measurement. Frequency of knowledge level was presented as threeÂ ordinal categories; good, moderate, and poor. Attitude of hypertension was presented as frequency in twoÂ categories; relatively positive and relatively negative.Results: Out of 120 respondents administered the questioner, 42.50% had good knowledge; 41.67% hadÂ moderate knowledge; 15.83% had poor knowledge related to hypertension prevention and 21.67% hadÂ good knowledge; 19.17% had moderate knowledge; 59.17% had poor knowledge related to managementÂ of hypertension. Hypertension attitude of respondents were 60.83% relatively positive in topics ofÂ hypertension prevention and 39.17% in topics of hypertension management.Conclusions: Respondents are knowledgeable about hypertension prevention but are less knowledgeableÂ about its management. Respondents have relatively positive attitudes towards hypertension prevention.Â In the other hand, respondents have more relatively negative attitudes towards its management.Â [AMJ.2016;3(2):222â9]DOI:Â 10.15850/amj.v3n2.801